Effect of Application and Intensity of Bevacizumab-based Maintenance After Induction Chemotherapy With Bevacizumab for Metastatic Colorectal Cancer: A Meta-analysis - Stein, A (2016)
BACKGROUND: The administration and intensity of bevacizumab-based maintenance therapy after induction treatment with bevacizumab is still a matter of debate. Thus, the present meta-analysis and an indirect comparison were performed to clarify these issues. PATIENTS AND METHODS: Trials evaluating a separately defined "maintenance phase," with randomization after the induction phase, were selected. Three trials of maintenance with bevacizumab with or without a fluoropyrimidine (CAIRO3, SAKK 41/06, and AIO KRK 0207) were analyzed regarding the effect on progression-free survival (PFS) and overall survival (OS) of any maintenance therapy compared with observation alone and different maintenance intensities (bevacizumab with or without fluoropyrimidine) compared with observation alone and between each other. RESULTS: Maintenance with bevacizumab with or without fluoropyrimidine after bevacizumab-based induction treatment for 4 to 6 months significantly improved PFS (hazard ratio [HR], 0.57; 95% confidence interval [CI], 0.43-0.75; P = .0004) and showed a trend toward prolonged OS (HR, 0.89; 95% CI, 0.78-1.02; P = .09) compared with observation alone. The effect on PFS increased with the intensity of the maintenance regimen (HR, 0.72; 95% CI, 0.60-0.85 for single-agent bevacizumab vs. HR, 0.45; 95%, CI 0.39-0.51 for combination therapy, both compared to observation alone). In contrast, the HRs for OS remained in the same range. A similarly improved PFS (HR, 0.63; 95% CI, 0.50-0.79) was shown for the more intensive maintenance therapy (bevacizumab and fluoropyrimidine) compared with bevacizumab alone. CONCLUSION: Bevacizumab-based maintenance therapy after induction chemotherapy with bevacizumab significantly improves PFS and showed a trend toward prolonged OS and should thus be considered, in particular, in patients with a response to induction treatment.